The Delone and McLean Information System Success Model: Investigating User Satisfaction in Learning Management System - Widyaningrum, Tutut; Sholihah, Qomariyatus; Haryono, Bambang Santoso (Universitas Pendidikan Ganesha, 2024)
E-learning system is designed with the consideration of the learners' needs in order to provide quality learning opportunities and positive learning experiences. This study aim to analyze user satisfaction and achieving overall system success. A survey on student satisfaction regarding the facilities and infrastructure in the learning activities indicates that approximately 18.3% are dissatisfied with the existing facilities.The objective of this study is to analyze the use and satisfaction of users of the Learning Management System (SIPEJAR) as an e-learning platform. The Research method was conducted with an explanatory quantitative approach and adopts the D&M IS Success Model as a theoretical framework. A total of 84 students were selected as respondents using the proportionate stratified random sampling method with Taro Yamane's formula at a significance level of 10% from the population of 542 undergraduate psychology students. The data was collected through questionnaires and analysis with SEM-PLS. The research results show that service quality has a positive and significant effect on usage, p-value of 0.029 but not for the system quality and information quality. System quality, information quality, and service quality have a significant effect on user satisfaction, p-values respectively, of 0.004, 0.038, and 0.003. Apart from that, system usage also has a significant influence on user satisfaction, p-value of 0.000. By identifying the usage and factors that influence user satisfaction, e-learning providers can focus their attention on improving specific aspects of the user experience and enhancing the overall learning process.